Organic porous solid as promising iodine capture materials - Yu, Ya-Nan; Yin, Zheng; Cao, Li-Hui; Ma, Yang-Min (Journal of inclusion phenomena and macrocyclic chemistry, 2022)
Facing the dual pressure of increasing global energy demand and heavy task in carbon emission reduction on schedule, nuclear renaissance is being seriously discussed as transitive choice before full renewable energy supply, yet there is a crucial concern about radioactive safety. The treatment of radioactive iodine is particularly important and challenging because of its high ratio in fission product, extremely long radioactive periods up to several millions of years, as well as easy diffusion in the whole ecosystem. Given that several challenge including easy sublimation, high water solubility, diverse existing species of I 2 , I − , I 2n+1 − and organic iodine, biocompatibility and strong aggregation in thyroid, rapid capture and permanent storage of iodine is requested. Comparing to inorganic adsorbents of zeolite and inorganic–organic hybrid MOFs, pure organic porous solid are emerging as new and promising iodine capture material. Their high iodine affinity and adsorption capacity, good stability in various environments, facile modification and functionalization, intrinsic structural flexibility guaranteed the outstanding performance in iodine capture. Four main categories of organic cages, supramolecular framework connected by weak interaction, covalent organic frameworks and polymers with intrinsic microporosity were summarized and discussed, from the viewpoints of design principles, iodine capture performance, and adsorbent-iodine interactions. As the main prospect, we hope this work will attracting more researchers to study porous organic materials and address the challenge of effective capture of radioactive iodine.